If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (G + 8) = 2X + H Reorder the terms: (8 + G) = 2X + H Remove parenthesis around (8 + G) 8 + G = 2X + H Reorder the terms: 8 + G = H + 2X Solving 8 + G = H + 2X Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + G = H + -8 + 2X Combine like terms: 8 + -8 = 0 0 + G = H + -8 + 2X G = H + -8 + 2X Reorder the terms: G = -8 + H + 2X Simplifying G = -8 + H + 2X
| 11(x-5)=(x+5) | | -21=2x-9 | | 191-v=89 | | -3(r+6)=-58 | | 3x+2=3(4)+2 | | 4y-4=35-6y | | z^4=28+96i | | 2x-18=3x+8 | | 231=165-y | | x=-12+-3y | | 10G+1=2k+(7X+Y) | | 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= | | 5x+17+7x-29=90 | | 5x+5=5y | | 120+-4.5=120 | | 2ax^2-4(a+1)x+4a+1=0 | | 4x^4-4x^3-17x^2-19x-6=0 | | 5x+4-8=18 | | 3n^2=-4n-1 | | 5(3k+2)=40 | | 6x-5+2x+43=90 | | 3+2(x+2)=15 | | 3(2y+1)=39 | | 2x+8=x+11 |